DOI: 10.31274/rtd-180813-12270
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polyphosphates and heat on selected Gram-positive bacteria important in foods

Abstract: INTRODUCTION 110 MATERIALS AND METHODS 113 Bacterial Culture Conditions and Media Preparation 113 Preparation of Bacteria 114 Thermal Inactivation and Enuderation 114 Effects of Catalase and Superoxide Dismutase 113 RESULTS 117 Recovery in Sealed Thermal Death Time Tubes Aerobic and Anaerobic Plate Counts Strictly Anaerobic Roll Tube Counts

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 122 publications
(197 reference statements)
0
1
0
Order By: Relevance
“…It was also noted that Staphylococcus incubated at pH 6 and 35°C demonstrated higher D‐ and z ‐value s than Salmonella indicating its longer thermal tolerance. Other studies (Jay, ; Knabel, ; Mai‐Prochnow, Clauson, Hong, & Murphy, ; Sun, ) reported that gram‐positive bacteria (e.g., Staphylococcus ) are relatively more heat resistant than gram‐negative bacteria (e.g., Salmonella ) due to the difference in the structure of their cell wall.…”
Section: Resultsmentioning
confidence: 99%
“…It was also noted that Staphylococcus incubated at pH 6 and 35°C demonstrated higher D‐ and z ‐value s than Salmonella indicating its longer thermal tolerance. Other studies (Jay, ; Knabel, ; Mai‐Prochnow, Clauson, Hong, & Murphy, ; Sun, ) reported that gram‐positive bacteria (e.g., Staphylococcus ) are relatively more heat resistant than gram‐negative bacteria (e.g., Salmonella ) due to the difference in the structure of their cell wall.…”
Section: Resultsmentioning
confidence: 99%